THE IMPACT OF DIGITAL LEARNING TECHNOLOGY ADAPTATION, PROFESSIONAL COMPETENCE, AND WORK COMMITMENT MODERATED BY ORGANIZATIONAL CULTURE ON STUDENT ACHIEVEMENT IN PUBLIC JUNIOR HIGH SCHOOLS - Hidayati, Andi (Universitas Ichsan Sidenreng Rappang, 2024)
The purpose of this study was to determine the influence of learning adaptation Tecnology digitalization, professional competence and work commitment moderated by organizational culture on student achievement in several public junior high schools in Makassar City. The sample was teachers at several public junior high schools in Makassar City, which were determined as many as 49 respondents. The data collection technique was through distributing questionnaires with data analysis techniques using Regression Moderated Analysis (MRA). The results of the study obtained findings that learning digitalization had a positive and significant effect on student achievement. Professional competence had a positive and significant effect on student achievement. Work commitment had a positive and significant effect on student achievement. The results of the moderation test obtained findings that organizational culture weakened and significantly influenced learning digitalization on student achievement. Organizational culture moderated or strengthened and significantly influenced professional competence on student achievement. Then organizational culture moderates or strengthens and significantly influences work commitment on student achievement in several public junior high schools in Makassar.